Temperament and Character Traits and Alexithymia in Patients with Multiple Sclerosis - Kuloglu, Murat; Saglam, Sema; Korkmaz, Sevda; Saglam, Sadullah; Gurok, M. Gurkan; Karti Ustun, Suzan; Bulut, Serpil (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2013)
Objective: In this study, we aimed to compare temperament and character traits and levels of alexithymia between multiple sclerosis (MS) patients and healthy individuals. Methods: Sixty patients with MS who were admitted to Firat University Hospital, Neurology Clinic and sixty age- and sex-matched healthy controls were enrolled in the study. Each participant met the inclusion criteria. The Temperament and Character Inventory (TCI), Toronto Alexithymia Scale (TAS-20), the Expanded Disability Status Scale (EDSS), and a semi-structured interview which investigated the clinical and socio-demographic features of the participants were administered to both patients and healthy individuals. Results: In terms of temperament and character components, scores of harm avoidance (HA), self-directedness (SD) and persistence (P) were found to be lower in MS group. In the analysis of subscales, scores of irregularity and fatigability were higher; scores of resourcefulness, and social approval were found to be lower in MS group. In terms of alexithymia levels, scores of difficulty identifying feelings and externally-oriented thinking, and total scores of alexithymia were lower in MS group than in controls. The TAS total scores of MS group showed negative correlation with SD (r=-0.307, p=0.017), and positive correlation with self-transcendence (ST) (r=0.291, p=0.024). Conclusion: The results of our study demonstrated that, there were differences between MS and control groups in terms of TCI parameters and the levels of alexitymia. Further studies are required to assess causal associations between these differences and MS. (Archives of Neuropsychiatry 2013; 50: 34-39)
Multipl skleroz hastalarında mizaç karakter özellikleri ve aleksitimi düzeyi
Keywords: Multiple Sclerosis; alexithymia; temperament; character; personality